Perlindungan Hukum Terhadap Pemenang Lelang Beritikad Baik yang Risalah Lelangnya dibatalkan Oleh Pengadilan - Suwandi, Dedy; Abib, Agus Saiful; Tamba S.P., Tumanda (Universitas Ekasakti, 2023)
Law Number 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land provides an opportunity for someone to be able to guarantee land and/or buildings for debts and receivables that they agree to. This mortgage right gives creditors the right to obtain repayment of certain money and gives them a priority position compared to other creditors. If the debtor breaks his contract, the creditor holding the first mortgage right has the right to sell the object of the mortgage right under his own authority through a public auction, and take payment of his receivables from the proceeds of the sale. The auction is often used as a lawsuit for third parties who have an interest in the collateral object being auctioned. Apart from that, the lawsuit also includes the Auction Minutes prepared by the Auction Officer. However, the Auction Minutes as an authentic deed are often canceled and considered to have never existed. When this happens, the auction winner becomes the party who suffers the most losses. As the auction winner has good intentions, he should receive protection for his ownership rights over the auction object.